A bipotentiostat based separation-free method for simultaneous flow injection analysis of chromium (III) and (VI) species. (20th May 2018) - Nellaiappan, Subramanian; Kumar, Annamalai Senthil
Abstract: Chromium(III) species is an essential micronutrient, whereas, its hexavalent form, Cr(VI) is considered to be a carcinogen. For the selective detection of Cr(III) in presence of Cr(VI), separation coupled spectroscopic techniques have been often used. For the first time in this work, we report a flow injection analysis coupled dual electrochemical detector (FIA-DECD) for separation-free detection of Chromium (III) and (VI) species. A gold nanoparticles decorated carbon nanofibres-chitosan modified electrode has been prepared by a quick and in-situ electrochemical deposition of Au 3+ ion in pH 7 phosphate buffer solution (PBS) and has been used as a dual electrochemical detector for Cr(VI)-reduction and Cr(III)-oxidation reactions in pH 2 PBS. Under an optimal hydrodynamic FIA-DECD condition, i.e., at applied potentials 0.1 V (for Cr(VI)-reduction) and 1 V vs Ag/AgCl (for Cr(III)-oxidation) and at a flow rate = 0.8 mL min −1, calculated linear range and detection limit values are; 0.1–100 ppm and 0.69 ppb (0.72 ppt for 20 μL sample loop volume) for Cr(III) and 0.1–100 ppm with detection limit, 0.32 ppb (0.33 ppt for 20 μL) for Cr(VI). No marked interference from other cations and anions like Cu 2+, Zn 2+, Cd 2+, Pb 2+, Co 2+, Ca 2+, Fe 2+, Mg 2+, NO3 −, NO2 −, SO3 2− and SO4 2− were noticed. Selective detection of Cr species (Cr(III) and Cr(VI)) in industrial waste water samples with data comparable to ICP-OES was demonstrated. Graphical abstract: